Pengaruh Komunikasi Terhadap Kepuasan Kerja dengan Lingkungan Kerja Sebagai Moderasi pada PT Puspita Agro Tirta - Intan Fadillah; Sari Marliani; July Yuliawati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
More than 40% of households in Indonesia rely on bottled drinking water (AMDK). The research aims to analyze the effect of communication and work environment on job satisfaction at PT Puspita Agro Tirta. The validity of the research data with quantitative methods. Data were obtained through a questionnaire involving 72 PT Puspita Agro Tirta employees, using Hair's formula, where the number of indicators × 5, which means the sample = 14 × 5 = 70 respondents for sampling. The analysis model uses SmartPLS-3.0 SEM based on PLS. The results showed that Communication has a significant effect on Job Satisfaction by 66.3%, where the delivery of tasks with the indicator “use of the right words” is the largest indicator based on the outer loading value, and the Work Environment is proven to moderate the relationship. The results of this study indicate that a comfortable work environment can improve employee performance despite the many pressures at work, and high employee satisfaction reflects the success and stability of the company. Therefore, Leaders need to improve responsiveness to feedback and concern for employees, as both are still low. Open and empathetic responses will improve communication and increase job satisfaction.